Manufacturing decline : how racism and the conservative movement crush the American Rust Belt - Hackworth, Jason R. (Columbia University Press, 2019)
Manufacturing Decline argues that antigovernment conservatives capitalized on-and perpetuated-Rust Belt cities' misfortunes by stoking racial resentment. Jason Hackworth traces how the conservative movement has used the imagery and ideas of urban decline since the 1970s to advance their cause.